Public space public life tool deternining the effectiveness of Quezon Memorial Circle as an urban public space - Orbon, Glenn T.; Evangelista, Alex Rey P. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
The designs of contemporary public spaces in the cities are most focused only on aesthetics and their function for special events and occasions, with minimal or no consideration on how people actually use and utilize such spaces on a normal basis. Emphasizing the importance of having quality public spaces in urban areas, this thesis aims to determine the effectiveness of the Quezon Memorial Circle (QMC) as an urban public space. Using the "Public Space Public Life" (PSPL) tool developed by Architect Jan Gehl, the researcher studied the life of QMC as a central urban park by looking into the existing conditions of the physical factors and elements of selected outdoor open spaces (Public Space) within the park and how people behave, move within, use and/or utilize (Public Life) the said spaces. Using observation studies as the main data gathering tool, documentation of the existing form and fabric as well as visual surveys on pedestrian paths and outdoor public spaces within QMC. Based on the results of the study, people from all demographics (gender, age and people with special needs) visit the QMC for various activities aside from relaxation and relief from the city life outside the said public space.The protection, comfort and enjoyment of park goers within the selected outdoor open spaces were also evaluated using Gehl's 12 Quality Criteria checklist. It was determined that the Quezon Memorial Circle, through its outdoor open spaces at the central area of the park, can be considered fairly effective as an urban public space only on the physical, environmental and aspects, with some site improvements that can be implemented in some areas to maintain its quality. This study can be further implemented together with other assessment tools to fully determine the effectiveness of other urban public spaces in the Philippines.
Thesis (Master of Architecture)--University of the Philippines Diliman